2015
DOI: 10.1111/jfq.12168
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal, Antiaflatoxin and Antioxidant Activity of Plant Essential Oils and Their In Vivo Efficacy in Protection of Chickpea Seeds

Abstract: This study presents the efficacy of six essential oils (EOs), viz. Carum carvi, Myristica fragrans, Melaleuca leucadendra, Cinnamomum camphora, Pelargonium odoratissimum and Cymbopogon citratus, as food preservatives based on antifungal, antiaflatoxin and antioxidant activity. The minimum inhibitory concentration of EOs against aflatoxigenic strain of Aspergillus flavus (LHP-10) and 13 other storage molds ranged between 1.25 and 6.0 μL/mL, while aflatoxin inhibition was observed at 1.0-5.0 μL/mL. EOs also exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Research findings from Deabes, Abou El‐Soud, and Abou El‐Kassem () indicate that 200 times the concentration (1,000 ppm) is required for the inhibition of A. flavus growth (71.666%) and aflatoxin production (24.980%). However, Prakash et al () indicate that 2 times less concentration (2.0 μl/ml) of this oil completely inhibited A. flavus (LHP‐10) and aflatoxin production in SMKY broth medium. These authors state that the concentration of caraway EO was effective in protecting chickpea seeds, during 6 months of storage.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Research findings from Deabes, Abou El‐Soud, and Abou El‐Kassem () indicate that 200 times the concentration (1,000 ppm) is required for the inhibition of A. flavus growth (71.666%) and aflatoxin production (24.980%). However, Prakash et al () indicate that 2 times less concentration (2.0 μl/ml) of this oil completely inhibited A. flavus (LHP‐10) and aflatoxin production in SMKY broth medium. These authors state that the concentration of caraway EO was effective in protecting chickpea seeds, during 6 months of storage.…”
Section: Resultsmentioning
confidence: 97%
“…Earlier studies have indicated the antimicrobial activity of caraway and juniper essential oils (Pepeljnjak, Kosalec, Kalođera, & Blažević, 2005;Farag, Daw, & Abo-Raya, 1989;Gniewosz, Kraśniewska, Woret, Kosakowska, 2013;Khalil, Ashour, Fikry, Singab, & Salama, 2018;Prakash et al, 2016;Razzaghi-Abyaneh et al, 2009;Zheljazkov et al, 2018). However, the antimicrobial activity of an oil depends on the geographical origin of the plant, the method of production, and the strain of tested microorganisms.…”
mentioning
confidence: 99%
“…During an antioxidant study by the DPPH assay, the IC 50 value of the C . camphora essential oil was found to be 31.85 µL/mL, whereas that for the reference butylated hydroxytoluene (BHT) was reported to be 7.6 µg/mL [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…C. camphora oil from Nepal also showed marginal activity against B. cereus and S. aureus, with a MIC = 313 µg/mL [49]. During an antioxidant study by the DPPH assay, the IC 50 value of the C. camphora essential oil was found to be 31.85 µL/mL, whereas that for the reference butylated hydroxytoluene (BHT) was reported to be 7.6 µg/mL [50].…”
Section: Sun Protection Factor (Spf)mentioning
confidence: 99%
“…In general, such limitations could effectively be overcome by incorporating plant extracts and bioactive compounds into emulsion-based delivery systems techniques. Emulsification technology can increase EOs' bioactivity due to their controlled release and increased bioavailability in the food systems (Prakash et al, 2016;Wan et al, 2019Wan et al, , 2020Wang et al, 2019a). Das et al (2021) reported that the encapsulation of Pimpinella anisum EO in chitosan nano-biopolymers increased antifungal and anti-aflatoxigenic efficacy due to effective interaction with the plasma membrane as a result of the greater surface area and smaller particle size.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%